Cooperative learning in ukrainian language classes - Sira, Larysa; Сіра, Лариса Іванівна (Barcelona, Spain, 2020)
Introduction. Among the important pedagogical problems presented to the teacher is the use of cooperative forms of organizing the students‘ learning. Modernization of modern education involves the formation of social skills in students and, above all, working together in pairs and groups with different number of people. Such educational cooperation brings up in students such traits as respect for others, the ability to evaluate the work of others or to express critical remarks in this regard, to change their opinion in the case of convincing arguments of other participants in joint work.
Keywords: матеріали конференцій